2016
DOI: 10.1186/s13229-016-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical morphological markers in children with autism: a structural magnetic resonance imaging study of thickness, area, volume, and gyrification

Abstract: BackgroundIndividuals with autism spectrum disorder (ASD) have been characterized by altered cerebral cortical structures; however, the field has yet to identify consistent markers and prior studies have included mostly adolescents and adults. While there are multiple cortical morphological measures, including cortical thickness, surface area, cortical volume, and cortical gyrification, few single studies have examined all these measures. The current study analyzed all of the four measures and focused on pre-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 90 publications
11
106
1
2
Order By: Relevance
“…One consistent change observed was an increased whole brain volume, with greater increases compared to controls observed among younger patients (Libero et al, 2016; Nordahl et al, 2013), which is consistent with the brain overgrowth theory and presence of restrictive and repetitive behaviours (Courchesne et al, 2003). Other consistent findings include an increased in brain volume (Riddle et al, 2017; Turner et al, 2016) in frontal and temporal lobes (Foster et al, 2015; Lim et al, 2015), increased CT in the frontal lobe (Hyde et al, 2009; Patriquin et al, 2016), increased SA (Ohta et al, 2016) and GI (Yang et al, 2016) globally, increased CSF and lateral ventricle volume (Haar et al, 2016; Shen et al, 2017), as well as reduced CC volume (Fredo et al, 2014; Haar et al, 2016). Finally, reduced cerebellum and cerebellar vermis volumes observed in multiple studies (Brun et al, 2009; Foster et al, 2015; Ure et al, 2016) is consistent with post‐mortem findings of reduced Purjinke cell numbers in autopsy studies of ASD.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…One consistent change observed was an increased whole brain volume, with greater increases compared to controls observed among younger patients (Libero et al, 2016; Nordahl et al, 2013), which is consistent with the brain overgrowth theory and presence of restrictive and repetitive behaviours (Courchesne et al, 2003). Other consistent findings include an increased in brain volume (Riddle et al, 2017; Turner et al, 2016) in frontal and temporal lobes (Foster et al, 2015; Lim et al, 2015), increased CT in the frontal lobe (Hyde et al, 2009; Patriquin et al, 2016), increased SA (Ohta et al, 2016) and GI (Yang et al, 2016) globally, increased CSF and lateral ventricle volume (Haar et al, 2016; Shen et al, 2017), as well as reduced CC volume (Fredo et al, 2014; Haar et al, 2016). Finally, reduced cerebellum and cerebellar vermis volumes observed in multiple studies (Brun et al, 2009; Foster et al, 2015; Ure et al, 2016) is consistent with post‐mortem findings of reduced Purjinke cell numbers in autopsy studies of ASD.…”
Section: Discussionmentioning
confidence: 74%
“…It was also unclear from the reviewed studies in Supplementary Table 2 as to the developmental trajectory of ASD, with four studies reporting accelerated thinning (Auzias et al, 2016; Koolschijn and Geurts, 2016; Wallace et al, 2015; Zielinski et al, 2014) and another four studies reporting slowed thinning (Doyle‐Thomas et al, 2013a; Khundrakpam et al, 2017; Sussman et al, 2015; Yang et al, 2016), reflecting the inconsistencies in ASD development observed for the whole brain volume (ICV). Despite this, increased CT was associated with poorer outcomes across multiple ASD severity measures, including social communication language ability (Khundrakpam et al, 2017; Sharda et al, 2016a, 2016b) and the ADOS (Moradi et al, 2017; Sato et al, 2013), supporting this measure as a useful biomarker of autism.…”
Section: Structural Biomarkers Of Asdmentioning
confidence: 99%
“…Not only do lGI brain-cognition relationships shift over adolescence, frontoparietal changes are instrumental in contributing to the maturation of motor response inhibition ability. Abnormal local cortical gyrification has been proposed as a possible endophenotype for numerous neuropsychiatric disorders (Fan et al, 2013; Hyatt et al, 2012; Liu et al, 2016; White and Gottesman, 2012; Yang et al, 2016) that arise in childhood and adolescence (Paus et al, 2008). Thus, it is of obvious interest to chart the normative trajectory of such associations, determine if particular regional gyrification patterns are cognitively specific, and seek evidence for what specific physiological processes might underlie the normative reductions in lGI that have been observed across multiple studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pocos estudios se han centrado en la franja de edad previa a la adolescencia. Los niños que participan en el presente estudio tienen edades comprendidas entre 8 y 12 años, etapa importante porque aún no se han producido cambios significativos estructurales y funcionales en el desarrollo cerebral característicos de la adolescencia (por ejemplo, cambios en la poda sináptica, en la mielinización, cambios volumétricos en estructuras subcorticales, diferencias sexuales en la conducta y en la cognición) (Giedd et al, 2009;Yang, Beam, Pelphrey, Abdullahi & Jou, 2016;Lenroot et al, 2007;Dennison et al, 2013).…”
Section: Vi-discusión Y Conclusionesunclassified
“…Los datos obtenidos en la comparación de ambos grupos de participantes respecto al TIV no revelaron ninguna diferencia significativa, resultado también aportado en otros estudios Hollander et al, 2005;Schumann et al, 2004;Say et al, 2014;Hardan et al, 2008a;Yang, Beam, Pelphrey, Abdullahi & Jou, 2016). De manera que, a nivel de TIV, en nuestro estudio tampoco se encontraron diferencias entre grupos ni en el volumen total cerebral, ni en el volumen de SG, volumen de SB pero sí una tendencia hacia la significación en el líquido cefalorraquídeo.…”
Section: Vi-discusión Y Conclusionesunclassified